2007
DOI: 10.1593/neo.07562
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Androgen-Insensitive Poorly Differentiated Tumors in the Transgenic Adenocarcinoma of Mouse Prostate Model

Abstract: Following castration, the transgenic adenocarcinoma of mouse prostate (TRAMP) model demonstrates rapid development of SV40-Tag-driven poorly differentiated tumors that express neuroendocrine cell markers. The cell population dynamics within the prostates of castrated TRAMP mice were characterized by analyzing the incorporation of 5-bromodeoxyuridine (BrdUrd) and the expression of SV40-Tag, synaptophysin, and androgen receptor (AR). Fourteen days postcastration, the remaining epithelial cells and adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 34 publications
6
62
0
Order By: Relevance
“…The other three tumors were not traceable to any lobe location due to their overwhelming large sizes. These data were consistent with two recent studies showing a preponderance of SYP positive NECa arising from VP in the TRAMP mice of both C57BL/6 and FVB backgrounds [9,10]. In contrast, the weight of macroscopic tumor-free VP lobes was only slightly increased in TRAMP mice compared to their wild type littermates at 24 WOA (Table 2 [15]), whereas the DLP lobes underwent significant expansion (more than doubled) in the TRAMP mice in one study where these lobes were compared side by side [14,15].…”
Section: Histological Characteristics Of Prostate Carcinogenesis In Tsupporting
confidence: 93%
See 2 more Smart Citations
“…The other three tumors were not traceable to any lobe location due to their overwhelming large sizes. These data were consistent with two recent studies showing a preponderance of SYP positive NECa arising from VP in the TRAMP mice of both C57BL/6 and FVB backgrounds [9,10]. In contrast, the weight of macroscopic tumor-free VP lobes was only slightly increased in TRAMP mice compared to their wild type littermates at 24 WOA (Table 2 [15]), whereas the DLP lobes underwent significant expansion (more than doubled) in the TRAMP mice in one study where these lobes were compared side by side [14,15].…”
Section: Histological Characteristics Of Prostate Carcinogenesis In Tsupporting
confidence: 93%
“…However, several recent studies have suggested that the poorly-differentiated neuroendocrine (NE)-like carcinomas (NECa) [9,10] belonged to a distinct lineage from the epithelial lesions, which included low and high grade PIN, WD to MD "adenocarcinomas" of the original classification by Dr. Greenburg [8]. Those epithelial lesions were recently termed "atypical hyperplasias of T-Ag" (AHT) to distinguish from the human prostate cancer pathogenesis because they did not invade adjacent tissues [9].…”
Section: Tramp Model Represents At Least Two Lineages Of Prostate Carmentioning
confidence: 99%
See 1 more Smart Citation
“…The acquisition of a neuroendocrine phenotype is frequently induced by the ADT commonly used for patients with advanced prostate adenocarcinoma (9,34,35) and is also observed in transgenic animal models of prostate cancer upon castration (36). These observations would suggest that the convergence of ADTinduced neuroendocrine transdifferentiation and increased expression of IL-1b underpins the propensity of prostate cancer cells to colonize the skeleton and eventually progress to secondary bone lesions.…”
Section: Resultsmentioning
confidence: 92%
“…undifferentiated cancer at 18 or 30 wks. Nevertheless, in the TRAMP model, it was found that prostate cancer could progress to an invasive neuroendocrine phenotype (42,43). It would be interesting to analyze the role of iodine in the acquisition of the neuroendocrine phenotype, since recent studies in neuroblastoma cells show that I 2 induces antiproliferative effects and sensitizes these cells to the differentiating effects of retinoic acid (9,44).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%